Technique and balance in elite judo - Rodriguez-Romo, G.; Stirling, J.; Zakynthinaki, M.; Lopez Diaz de Durana, A.; Cordente Martinez, C.; Sillero Quintana, M.; Sampedro Molinuevo, J. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Balance is fundamental in judo, both in attack when trying to break the opponent`s balance and in the defense of such attacks. Tools from dynamical systems have recently been used to model the process of regaining balance following a perturbation form quiet stance (Zakynthinaki et al, 2008; Stirling and Zakynthinaki, 2004). The aim of this study was to apply the model of Stirling and Zakynthinaki (2004) to look at the connection between the balance of elite judokas and their technique both in attack and defense. Methods 5 judokas of the Spanish National Team were studied. The ground reaction forces resulting from the judoka being perturbed from quiet upright stance, for the two legged and single legged condition (Zakynthinaki et al, 2008; Stirling et al, 2007) were modeled and analyzed. With the use of a force platform the maximum correctable angles between the resultant ground reaction forces and the vertical in the anteroposterior and mediolateral directions were obtained. A closed critical curve (Stirling and Zakynthinaki, 2004) was then fit through the maximum correctable angles (for greater angles than these the judoka falls over). The curve was analyzed to find asymmetries. Each judoka also completed a questionnaire regarding their preferred techniques, with video being taken both of these techniques and also all the experiments. Results It was observed that the favored side (in the case of the two legged experiment) or leg (in the case of one legged experiment) for balance was connected with technical features of the preferred techniques of the judokas. In some of the judokas this preference was shown to be strong. Discussion Non-symmetric behavior caused by muscle imbalances, postural problems, structural problems and differences in the ranges of motion on either side of the body have been identified via the critical curve (Zakynthinaki et al, 2008; Stirling and Zakynthinaki, 2004). Our research has shown how these methods can be used to identify competitive strengths and weaknesses for addressing and correcting via training in elite judo (Stirling and Zakynthinaki, 2005; A. López Díaz de Durana, 2009).